2014
DOI: 10.1002/adsc.201400459
|View full text |Cite
|
Sign up to set email alerts
|

pseudo Enantiomeric Carbohydrate Olefin Ligands – Case Study and Application in Kinetic Resolution in Rhodium(I)‐Catalysed 1,4‐Addition

Abstract: In order to investigate significant differences in asymmetric induction for pseudo enantiomeric carbohydrate olefin ligands in rhodium(I)catalysed 1,4-addition reactions, we designed a set of new olefin ligands differing in relative configuration and pyranoside conformation. With these, we have successfully elucidated structural requirements for metal binding and also identified an improved alternative for one pseudo enantiomer. Furthermore, we report the efficient kinetic resolution of a racemic 4-hydroxycycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Coordination of chiral alkene ligands to rhodium metal in the catalysis of 1,4-addition of boronic acids, as seen in the previous example, offers an excellent opportunity to control asymmetric induction through ligand design. Grugel et al sought to prepare novel alkene phosphinite ligands derived from carbohydrates, such as d -glucose and d -galactose . The authors studied structural constraints affecting enantioselectivity, such as the impact of axial versus equatorial positions for the ring substituents in the available pyranoside conformers.…”
Section: Resolution Methods For the Synthesis Of Chiral Cyclopentenonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coordination of chiral alkene ligands to rhodium metal in the catalysis of 1,4-addition of boronic acids, as seen in the previous example, offers an excellent opportunity to control asymmetric induction through ligand design. Grugel et al sought to prepare novel alkene phosphinite ligands derived from carbohydrates, such as d -glucose and d -galactose . The authors studied structural constraints affecting enantioselectivity, such as the impact of axial versus equatorial positions for the ring substituents in the available pyranoside conformers.…”
Section: Resolution Methods For the Synthesis Of Chiral Cyclopentenonesmentioning
confidence: 99%
“…Grugel et al sought to prepare novel alkene phosphinite ligands derived from carbohydrates, such as D-glucose and D-galactose. 56 The authors studied structural constraints affecting enantioselectivity, such as the impact of axial versus equatorial positions for the ring substituents in the available pyranoside conformers. Interestingly, it was found that the direction of asymmetric induction was primarily determined by the direction of the phosphinite substituent relative to the pyranoside ring (i.e., above or below).…”
Section: Resolutions By Chemical Derivatizationsmentioning
confidence: 99%
“…The results are illustrated in Table 87. 263 Highly enantioselective additions of differently substituted arylboronic acids 2 to diverse b-nitro-based Michael acceptors 180a-i under the control of a novel and efficient Rh-bicyclo[2.2.1]-diene catalyst (S/C (substrate/catalyst) up to 1000) were successfully performed, affording b,b-diaryl nitroethanes 268a-z in good to high yields (62-99%) and with high to excellent enantioselectivities (85-97% ee) (Table 88). 264 This strategy was expanded to 2-heteroarynitroolefins and 2-alkylnitroolefins, which also gave the desired products with high enantioselectivities and yields via Rh-L50 complex catalysis.…”
Section: Table 48mentioning
confidence: 97%
“…The modularity of the ligand synthesis and the availability of different carbohydrate precursors allowed Boysen and co-workers to conduct extensive structure-activity studies, which also led to pseudo-enantiomeric ligand systems. 26 , 27 …”
Section: Selected Examplesmentioning
confidence: 99%